Opinion of the Graduated Population about their Training and Updating Needs of the Library and Documentation Career of the National University of Costa Rica - Barboza Jiménez, Lucrecia (2020)
The objective of this study is to identify the opinions of the population that graduated from the National University's Library and Documentation career, with respect to their education, and needs for updating and training to strengthen academic and work skills. This research had a quantitative focus and was descriptive; data collection was done through a digital questionnaire applied to 60 people who graduated between 2010 and 2018. With the results, it was possible to obtain a profile of the graduate and data on the relevance and availability of means and resources for learning in the career, current job placement, professional performance, expectations for development, professional improvement and updating, and some comments and suggestions for improvement.